Psychopathology mediates between maltreatment and memory functioning in Burundian refugee youth. (August 2021) - Scharpf, Florian; Mueller, Sven C.; Masath, Faustine Bwire; Nkuba, Mabula; Hecker, Tobias
Abstract: Background: The detrimental impact of child maltreatment on children and adolescents' academic achievement and later socioeconomic wellbeing is well known. However, it is still unclear (1) whether maltreatment is actually linked to youth's long- and short-term memory deficits and (2) whether potential impairments are due to maltreatment per se or related psychopathology. Objective: Based on the Attentional Control Theory, we investigated a mediational model in which maltreatment would be related to psychopathology (internalizing symptoms, posttraumatic stress symptoms, posttraumatic cognitions), which would in turn be related to impaired memory functioning. Participants and setting: We drew on a sample of 155 Burundian refugee youth (aged 11 to 15) currently living in refugee camps in Tanzania and at high risk of experiencing ongoing maltreatment by parents. Methods: Youth reported on their experiences of maltreatment and psychopathology in structured clinical interviews and completed visuospatial memory tasks involving a short-term and a working memory component (Corsi Block Tapping Test) and delayed recall from long-term memory (Rey-Osterrieth Complex Figure). Results: Structural equation modeling showed that psychopathology mediated the association between increased maltreatment and reduced working memory capacity ( β = −0.07, p = .02), with a trend towards mediation for short-term memory ( β = −0.05, p = .06). Higher levels of maltreatment, but not psychopathology, were directly linked to long-term memory deficits ( β = −0.20, p = .02). Conclusions: Preventive efforts targeting maltreatment and interventions focusing on related psychopathology are needed to counter memory deficits and their potential negative implications for academic and socioeconomic outcomes.